Validation of two nurse-based screening tools for delirium in elderly patients in general medical wards - Manuela Bergjan; Max Zilezinski; Torsten Schwalbach; Christiana Franke; Hebun Erdur; Heinrich Jakob Audebert; Armin Hauß (BMC, 2020)
Abstract Background Delirium is an acute disturbance characterized by fluctuating symptoms related to attention, awareness and recognition. Especially for elderly patients, delirium is frequently associated with high hospital costs and resource consumption, worse functional deterioration and increased mortality rates. Early recognition of risk factors and delirium symptoms enables medical staff to prevent or treat negative effects. Most studies examining screening instruments for delirium were conducted in intensive care units and surgical wards, and rarely in general medical wards. The aim of the study is to validate the Nursing Delirium Screening Scale (Nu-DESC) and the Delirium Observation Screening Scale (DOS) in general medical wards in a German tertiary care hospital, considering predisposing delirium risk factors in patients aged 65 and older. Methods The prospective observational study including 698 patients was conducted between May and August 2018 in two neurological and one cardiology ward. During their shifts, trained nurses assessed all patients aged 65 or older for delirium symptoms using the Nu-DESC and the DOS. Delirium was diagnosed according to the DSM-5 criteria by neurologists. Patient characteristics and predisposing risk factors were obtained from the digital patient management system. Descriptive and bivariate statistics were computed. Results The study determined an overall delirium occurrence rate of 9.0%. Regarding the DOS, sensitivity was 0.94, specificity 0.86, PPV 0.40 NPV 0.99 and regarding the Nu-DESC, sensitivity was 0.98, specificity 0.87, PPV 0.43, NPV 1.00. Several predisposing risk factors increased the probability of delirium: pressure ulcer risk OR: 17.3; falls risk OR: 14.0; immobility OR: 12.7; dementia OR: 5.38. Conclusions Both screening instruments provided high accuracy for delirium detection in general medical wards. The Nu-DESC proved to be an efficient delirium screening tool that can be integrated into routine patient care. According to the study results, pressure ulcer risk, falls risk, and immobility were risk factors triggering delirium in most cases. Impaired mobility, as common risk factor of the before mentioned risks, is well known to be preventable through physical activity programmes.